PRELIMINARY SOMMA DATA: COGNITIVE AND PHYSICAL FUNCTION RELATIONSHIPS IN OLDER ADULTS. (20th December 2022) - Kritchevsky, Stephen; Newman, Anne; Cawthon, Peggy; Mau, Theresa; Hepple, Russell T; Coen, Paul; Goodpaster, Bret; Cummings, Steven
Abstract: We used canonical correlation (n=424) to examine the relationships between a set of physical function measures (400m usual pace, chair stands/sec, 4m walk pace, standing balance times, VO2 peak, muscle power, four-square step test (FSST) time, stair climb time and stair climb power) and a set of cognitive measures (Trail Making Test B (sec), Digit Symbol Substitution Test (DSST), the Montreal Cognitive Assessment, and California Verbal Learning Test). Canonical correlation derives synthetic variables comprised of linear combinations within each set of variables (physical and cognitive) that maximize the correlations between synthetic variables. The FSST was most strongly correlated with the cognitive synthetic variable (- 0.42). The DSST score was the cognitive measure most strongly correlated with the physical synthetic variable (0.48). It is notable that only the timed cognitive and physical tests are inter-associated